Multi-Criteria Analysis for Selecting Solid Waste Management Concept Case Study: Rural Areas in Sentani Lake Region, Jayapura - Alfred Benjamin Alfons; Tri Padmi (Universitas Trisakti, 2018)
Aim: This study aims to identify, develop, and determine the most suitable concept of solid waste management to be applied in Ifale Village, Yobeh Village, Putali Village, Atamali Village, and Asei Besar Village. Until now, the application of solid waste management system in Jayapura is still far from what people expected since it has been unable to serve the communities who live in rural areas on the islands around Sentani Lake. As a result, 12,554.38 liters/day of solid waste generated by the community in these regions is left untreated. Methodology and Results: The study is using the Analytic Hierarchy Process (AHP) method. The AHP calculations show that the idea of handling solid waste in an integrated treatment facility—following the initial sorting on the household scale—has the highest priority weight (2.05) compared to the other alternatives. Hence, it has been chosen as the best solid waste management concept that can be applied to the study sites. Based on the results as well, the main criteria to be considered include the environmental aspects, social aspects, and technical aspects with each weighing value of 0.534, 0.186, and 0.147, respectively. Conclution, significans and impact study: The sub-criteria with the highest priorities to be considered in making the decision are the soil pollution (due to produced leachate), air pollution (potentially in the form of stench and gas emissions), the transmission of disease vectors, public participation, and the operational convenience.